Rational construction of a CdS/reduced graphene oxide/TiO2 core–shell nanostructure as an all-solid-state Z-scheme system for CO2 photoreduction into solar fuels. Issue 107 (19th October 2015) - Kuai, Libang; Zhou, Yong; Tu, Wengguang; Li, Ping; Li, Haijin; Xu, Qinfeng; Tang, Lanqin; Wang, Xiaoyong; Xiao, Min; Zou, Zhigang
Abstract : An all-solid-state Z-scheme was constructed for the photocatalytic reduction of CO2, consisting of CdS and TiO2 as photocatalysts, and reduced graphene oxide as a solid electron mediator. Abstract : Mimicking natural photosynthesis in green plants, an all-solid-state Z-scheme was constructed for photocatalytic reduction of CO2 in the presence of water vapor, consisting of CdS nanospheres (CdS NSs) and TiO2 nanoparticles as photocatalysts, and reduced graphene oxide (rGO) as a solid electron mediator. In this Z-scheme system, the photogenerated electrons from the conduction band of TiO2 transfer to rGO, and then recombine with the existing holes of CdS NSs, allowing the photo-generated electrons to enrich on the CdS semiconductor and holes on the TiO2 . The photocatalytic efficiency of the Z-scheme system exhibits remarkable enhancement relative to pure CdS, CdS/TiO2, and CdS/rGO.